Application of Al-Quran Learning with the Tartila Method for Junior High School Students in Sibolga - Ellisa Fitri Tanjung; Isra Hayati; M. Fauzi Hasibuan (STAI Hubbulwathan Duri, 2022)
Al-Quran is a holy book that is the main source of law and life guidelines for Muslims. As the main source, the Qur'an has various privileges for mankind, including management rights, both in terms of mahdhah worship (vertical relationships with Allah swt.) and ghairumahdhah worship (horizontal relationships with fellow humans). This study was conducted in class IX students of a Madrasah Tsanawiyah (Islamic junior high school) in Sibolga. This study aims to determine the advantages and disadvantages of the Tartila method in the ability to read and write the Qur’an. To collect the data, this study used observation, while to analyze the data, the Miles and Huberman model was used. This research is expected to reveal the application of the Tartila method in improving the ability to read and write the Qur'an. The results of this study provide new contributions, especially regarding the benefits of the Tartila Method in studying the Qur'an. The results of this study can be useful for the students, as discourse and scientific development about Al-Quran learning, as input and consideration in developing Al-Quran learning, and as an evaluation material for the ongoing Al-Quran learning process.